2020
DOI: 10.1002/rem.21660
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm mediated degradation of commercially available LDPE films by bacterial strains isolated from partially degraded plastic

Abstract: Biodegradation is an attractive approach for the elimination of synthetic polymers, pervasively accumulated in natural environments and generating ecological problems. The present work investigated the degradation of low‐density polyethylene (PE) by three Bacillus sp., that is, ISJ36, ISJ38, and ISJ40. The degree of biodegradation was assessed by measuring hydrophobicity, viability, and total protein content of bacterial biofilm attached to the PE surface. Although all three bacterial strains were able to esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…presents the results of the biodegradation tests carried out without pre-treatment, and no reduction in biomass was observed in the control sample. The study's conclusions were consistent with previous research byGupta and Devi (2020), who identified three bacterial strains (ISJ36, ISJ38, and ISJ40) isolated from soil-adherent polyethylene film collected from landfill sites Khandare et al (2021). noted that over a period of 90 days, four marine bacterial isolates (H-237, H-255, H-256, and H-265) experienced weight loss of 1.4%, 1.72%, 1.26%, and 0.97%, respectively.…”
supporting
confidence: 92%
“…presents the results of the biodegradation tests carried out without pre-treatment, and no reduction in biomass was observed in the control sample. The study's conclusions were consistent with previous research byGupta and Devi (2020), who identified three bacterial strains (ISJ36, ISJ38, and ISJ40) isolated from soil-adherent polyethylene film collected from landfill sites Khandare et al (2021). noted that over a period of 90 days, four marine bacterial isolates (H-237, H-255, H-256, and H-265) experienced weight loss of 1.4%, 1.72%, 1.26%, and 0.97%, respectively.…”
supporting
confidence: 92%